The Influence of Principal Managerial Competence on Teacher Performance at Schools in Bandar Lampung - May, Lourena Fitri; Abdurrahman, Abdurrahman; Hariri, Hasan; Sowiyah, Sowiyah; Rahman, Bujang (Universitas Islam Negeri Raden Intan Lampung, 2020)
Any improvement effort made without the support of quality teacher performance will not possibly work well to help enhance high-quality education. High teacher performance is influenced by many factors. Theoretically, one important factor is principal managerial competency. However, how this factor influences teacher performance is under-researched, particularly in Bandar Lampung schools. This study aimed at investigating the influence of principal managerial competence on teacher performance in public vocational high schools in Bandar Lampung. This study used a quantitative research design, using a questionnaire of which its validity and reliability were ensured before data collection. The samples of the research were 88 teachers from nine vocational high schools in Bandar Lampung City, Lampung Province, Indonesia. The data collected were analyzed using descriptive statistics and simple regression, with the help of SPSS version 24. Results showed that principal managerial competence positively and significantly influenced teacher performance in public vocational high schools in Bandar Lampung. This study recommends the whole stakeholders to pay more attention and to evaluate the principals’ performance.